Ecritures mémorielles et crise de la représentation : les écrivants descendants de harkis - Giulia Fabbiano (Amnis, 2007)
If the Harkis have been for a long time expelled from history and have been spoken of by others (by scholars on the one hand and by “Nostalgerians” activists on the other hand), lately they have been questioning this history and have spoken through their own voice. This transition from a second- hand discourse to a self-assumed one can be chronologically associated with the irruption of a new kind of mnemonic manifestation: (auto)biographical narratives. Writing becomes an instrument of communication and diffusion of an injured memory, in other words an activity which can inform on the contemporary processes of memorial and identity out-coming.